Dissociation and microsolvation of bisulfate anion. (7th February 2020) - Ashraf, Hamad; Hua, Cheng; Zhang, Yun‐Hong
Abstract: Bisulfate anion has vast applications in industrial and environmental chemistry. Its dissociation to sulfate anion has been studied computationally and by size‐selected clusters. In this study, Micro‐Raman spectroscopy is applied at different relative humidity (RH)% on small droplets of aqueous solutions of NaHSO4, NH4 HSO4, and H2 SO4 to explore the dissociation of HSO4 ‐ experimentally in bulk and supersaturated state. Our cumulative experimental results support the conclusion obtained from gas‐phase cluster study that HSO4 ‐ starts dissociating at very low number of water molecules (H2 O 1). However, dissociation of HSO4 ‐ is found dependent on the cation attached with this weak acid. The magnitude of dissociation is found as NH4 HSO4 ≈ H2 SO4 > NaHSO4 . In addition, studying the hydration process of HSO4 − in the presence of three different cations enabled us to observe various species in three systems. Theoretical values obtained from extended aerosol inorganic model supports the experimental results. Abstract : In this work, dissociation and microsolvation of bisulfate anion is explored. Dissociation of anion starts in the presence of one water molecule, which depends on the nature of counter cation. Moreover, various hydrogen bonded species are identified in each system (NaHSO4, NH4HSO4, and H2SO4).